The growing prominence of deliberative mini-publics and their impact on democratic government. Issue 2 (3rd April 2022) - Farrell, David M.; Field, Luke
ABSTRACT: In the opening lines of Ruling the Void Peter Mair states that '[t]he age of party democracy has passed'. In his eyes political parties are failing and with them democracy itself. This paper addresses Mair's concerns about the state of democracy. We review the latest evidence on how democracies have been innovating over the past twenty years or more, with particular attention to reforms that seek to bring citizens into the heart of discussions about constitutional and institutional reforms and significant policy issues. We show how deliberative mini-publics are becoming a more common feature of democratic government today, and, in some instances, how they are being embedded into the democratic system. We assess the implications for the state of state of democratic government today.